By-pass arterial fémoro tibial distal en extremidades con isquemia severa: a propósito de 19 observaciones - Nozar, José; Gateño, Nisso; Goller, Wolfgang; Abó, Juan C (Cirugía del Uruguay, 1978)
Distal femoro-tibial arterial by-pass in limbs affected by severe ischemia. 19 cases,. By-pass to distal sectors of limb trunks was performed in 19 cases, with an inverted autologous safena vein. Preoperatory angiogram is of fundamental importance in surgical indication, · for this procedure is counter-indicated in cases in which the plantar arch is non-existant. Permeability at the time the patients were discharged from hospital was 84 % . Follow-up ranged from 3 months to 8 years. There were 3 cases of distant obstructions, in all probability due to intima! fibroplasia. Distant permeability was 63 %and cummulative permeability for the 8 years, 52 %No deaths occurred. The authors' conclusion is that it is worth searching for a single trunk before proceeding to amputation of limb.